Expression Analysis of Ermin and Listerin E3 Ubiquitin Protein Ligase 1 Genes in Autistic Patients - Shiva, Shadi; Gharesouran, Jalal; Sabaie, Hani; Asadi, Mohammad Reza; Arsang-Jang, Shahram; Taheri, Mohammad; Rezazadeh, Maryam (Frontiers in Molecular Neuroscience, 2021)
Autism Spectrum Disorder is a severe neurodevelopmental disorder that involves social interaction defects, impairment of non-verbal and verbal interactions, and limited interests along with stereotypic activities. Its incidence has been increasing rapidly in recent decades. Despite numerous attempts to understand the pathophysiology of ASD, its exact etiology is still unclear. Recent data shows the role of accurate myelination and translational regulation in ASD's pathogenesis. In this study, we assessed Ermin (ERMN) and Listerin E3 Ubiquitin Protein Ligase 1 (LTN1) genes expression in Iranian ASD patients and age- and gender-matched healthy subjects' peripheral blood using quantitative real-time PCR to recognize any probable dysregulation in the expression of these genes and propose this disorder's mechanisms. Analysis of the expression demonstrated a significant ERMN downregulation in total ASD patients compared to the healthy individuals (posterior beta = -0.794, adjusted P-value = 0.025). LTN1 expression was suggestively higher in ASD patients in comparison with the corresponding control individuals. Considering the gender of study participants, the analysis showed that the mentioned genes' different expression levels were significant only in male subjects. Besides, a significant correlation was found between expression of the mentioned genes (r = -0.49, P < 0.0001). The present study provides further supports for the contribution of ERMN and LTN1 in ASD's pathogenesis.